To What Extent Can Problem-Based Learning Drive Students’ Critical Writing Skills? - Moh. Yamin; Vivi Aulia (Universitas Hamzanwadi, 2025)
This study investigates the extent to which Problem-Based Learning (PBL) can enhance students’ critical writing skills in an English as a Foreign Language (EFL) context. Eleven undergraduate students participated in the study and produced a critical writing assignment that served as the primary data source. Using a descriptive qualitative design, the analysis focused on examining how students formulated research problems, constructed thesis statements, and developed arguments, counter-arguments, evidence, and interpretations within their essays. Manual coding was applied to identify recurring patterns of critical thinking indicators, followed by content analysis to interpret the depth and coherence of students’ written responses. The findings reveal that PBL provides a meaningful scaffold for strengthening higher-order thinking and guiding students to move beyond descriptive writing. Most students demonstrated improvement in identifying issues, articulating them as topic sentences, and developing logically connected discussions supported by reasoning and data. Although variations in writing quality were evident, the overall results indicate that PBL fosters critical engagement, enhances argumentative organisation, and supports learners’ development of analytical perspectives in writing. These findings suggest that PBL is a promising pedagogical approach for cultivating students’ critical writing competence and call for further research on integrating PBL-based critical thinking instruction in EFL writing classrooms.